THE METHODOLOGY BEHIND THE BOOK - IMAGINED REALITIES AN EXPERIMENT IN HUMAN-AI CO-CREATION - Wahajuddin, Farah (International Journal of Research -GRANTHAALAYAH, 2025)
This paper explores Imagined Realities, an experimental project that investigates the dynamic interplay between human creativity and artificial intelligence in the realm of storytelling. Conducted at Jawaharlal Nehru Architecture and Fine Arts University, Hyderabad, the initiative brought together interior design students and OpenAI's ChatGPT-4 to collaboratively generate narratives based on a curated set of AI-generated images and character briefs. The dual-phase study examined both human-written and AI-generated stories through a detailed rubric focusing on narrative structure, spatial and sensory language, emotional resonance, and character analysis. By integrating pedagogical goals from the students’ communication skills curriculum with cutting-edge generative AI technology, the project aimed to deepen self-expression, storytelling proficiency, and critical engagement with technology. The comparative analysis revealed key differences in emotional nuance, spatial perception, and cultural depth between human and machine-authored texts. The resulting book, Imagined Realities, serves not only as a creative anthology but as a reflective commentary on the evolving landscape of human-AI collaboration in the arts. Ultimately, this project underscores the complementary strengths of human intuition and AI logic while prompting vital discourse on authorship, creativity, and the future of storytelling.